Case Report: Adjuvant splenic irradiation therapy effectively eliminates donor-specific antibodies and reverses refractory early active antibody-mediated rejection after presensitized kidney transplantation - Guo, Zhiliang; Sa, Rula; Zhao, Guangyuan; Che, Fuheng; Guo, Hui; Zhu, Lan; Chen, Gang (Frontiers in Immunology, 2025)
In presensitized kidney transplantation with positive donor-specific antibody (DSA), the activation of immune memory responses leads to a significant increase in DSA levels, followed by early active antibody-mediated rejection (early aAMR). For some patients, it is difficult to eliminate DSA and reverse aAMR after conventional treatments such as plasmapheresis (PP) and intravenous immunoglobulin (IVIG). Here we report three cases of successful reversal of refractory early aAMR after DSA-positive presensitized kidney transplantation by using adjuvant splenic irradiation therapy. At 1 to 2 weeks after kidney transplantation, all three of our recipients experienced a significant increase in DSA levels, accompanied by deterioration of renal allograft function. The aAMR of two patients was diagnosed by renal biopsy, and the other was diagnosed clinically. After 5 to 11 sessions of PP/IVIG treatment, the DSA levels of all three patients failed to decrease, or even continued to rise. Therefore, in addition to PP/IVIG treatment, all three patients received 10 sessions of low-dose repetitive splenic irradiation (50cGy per session) as adjuvant therapy. As a result, the levels of all DSAs began a continuous decline, and renal function gradually returned to normal or approached normal. Eventually, all three patients recovered and were discharged from the hospital. During the 14- to 75-month follow-up period, the DSA of two patients became negative, while that of the remaining one patient remained at a low level. Renal function was stable during the follow-up period. Thus, when early aAMR that resists conventional treatment occurs after presensitized kidney transplantation, splenic irradiation may be an important adjuvant treatment option.